Dampak Eskalasi Konflik Rusia-Ukraina terhadap Keamanan Nasional Ukraina - Isnain, Fadhilah; Wicaksono, Arief (Journal of International and Local Studies, 2023)
Abstract: The annexation of Crimea led to a prolonged conflict in Donbas, escalated the conflict, and resulting in Russia's invasion of Ukraine. This study aims to identify and analyze the impact of the escalation of the Russia-Ukraine conflict to the Ukraine national security in 2014-2022. This researh was conducted qualitatively, focusing in analizyng data that ranged from news articles to official statements from both involved countries. Through utilizing the concept of national security, researchers found that the escalation of the conflict between Russia and Ukraine has caused enormous losses to Ukraine which include threats to Ukraine's territorial sovereignty, problems in the economic field and the occurrence of humanitarian crises. Thus, causing instability in Ukraine's national security. Keywords: Russia, Ukraine, natinal security, conflict, war